Circadian rhythms of risk factors and management in atherosclerotic and hypertensive vascular disease: Modern chronobiological perspectives of an ancient disease. (2nd January 2023) - Geng, Yong-Jian; Smolensky, Michael H.; Sum-Ping, Oliver; Hermida, Ramon; Castriotta, Richard J.
ABSTRACT: Atherosclerosis, a chronic inflammatory disease of the arteries that appears to have been as prevalent in ancient as in modern civilizations, is predisposing to life-threatening and life-ending cardiac and vascular complications, such as myocardial and cerebral infarctions. The pathogenesis of atherosclerosis involves intima plaque buildup caused by vascular endothelial dysfunction, cholesterol deposition, smooth muscle proliferation, inflammatory cell infiltration and connective tissue accumulation. Hypertension is an independent and controllable risk factor for atherosclerotic cardiovascular disease (CVD). Conversely, atherosclerosis hardens the arterial wall and raises arterial blood pressure. Many CVD patients experience both atherosclerosis and hypertension and are prescribed medications to concurrently mitigate the two disease conditions. A substantial number of publications document that many pathophysiological changes caused by atherosclerosis and hypertension occur in a manner dependent upon circadian clocks or clock gene products. This article reviews progress in the research of circadian regulation of vascular cell function, inflammation, hemostasis and atherothrombosis. In particular, it delineates the relationship of circadian organization with signal transduction and activation of the renin-angiotensin-aldosterone system as well as disturbance of the sleep/wake circadian rhythm, as exemplified by shift work, metabolic syndromes and obstructive sleep apnea (OSA), as promoters and mechanisms of atherogenesis and risk for non-fatal and fatal CVD outcomes. This article additionally updates advances in the clinical management of key biological processes of atherosclerosis to optimally achieve suppression of atherogenesis through chronotherapeutic control of atherogenic/hypertensive pathological sequelae.